PENGARUH JELLY GLUKOMANAN TERHADAP RASA KENYANG DAN PENURUNAN BERAT BADAN PADA PROGRAM DIET RENDAH KALORI (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Glucomannan is a water-soluble dietary fiber that can suppress hunger so that it can reduce appetite and have an effect on weight loss. This study aims to determine the effect of glucomannan jelly on satiety and weight loss in adults undergoing a low-calorie diet program. True-experimental with control group pre-post test. Respondents get 1500 Kcal diet, glucomannan jelly for the treatment group and placebo jelly for the control group for 5 days. Body weight was measured at the beginning and end of the study. The level of satiety was measured every day before eating, 60, 90, and 120 minutes after jelly consumption using 100 mm Satiety Labeled Intesity Magnitude (SLIM) bipolarscale. Data were analyzed using T-Test and Mann Whitney test. At 30 minutes after consuming jelly, the satiety scale in the treatment group (29,98) was higher than the control group (22,60). The satiety scale continued to decrease until 120 minutes after jelly consumption in both groups. There was no difference in satiety scale between two groups (p = 0.421), but the satiety scale in the treatment group was consistently higher than the control group. The mean of body weight in the two groups decreased, but was not significantly different (p = 0.497). Glucomannan jelly can induce satiety longer so it can be used in a low-calorie diet program. It needs to be done with an intervention program with a longer duration to see the long-term effect of consuming glucomannan jelly on body weight.